A concept map for urban art (REVISTA NODO, 2011)
By means of various art references and conceptual meditations, the author clarifies how the coexistence of tangible objects and ephemeral artistic actions within public space of contemporary cities can produce a field of multiple possibilities. Since the wide range of artworks present today in urban contexts include those with a commemorative or historical character, the ones more interested in aesthetics, the temporal interventions dealing with imprints and markings on the territory, and those of an anthropological approach based on human groups, the article proposes a four-concept structure to organize art manifestations from which it is possible to map them like monuments, sculptures, interventions, and community projects. As a conclusion, the concept map sketched in the article allows for an extensive and clear vision or urban art and its current possibilities; a map that could (and should) be crossed horizontally, given that a site-specific art intervention can become  such an emblematic object like a national monument.
Keywords: City; art; monuments; sculptures; interventions; community art projects